2014
DOI: 10.3892/or.2014.3197
|View full text |Cite
|
Sign up to set email alerts
|

Presence of the minor EGFR T790M mutation is associated with drug-sensitive EGFR mutations in lung adenocarcinoma patients

Abstract: Abstract. The T790M mutation in the epidermal growth factor receptor (EGFR) gene is known to be associated with the acquired resistance of lung adenocarcinoma patients to EGFRtyrosine kinase inhibitors (EGFR-TKIs). The minor T790M mutant allele is occasionally detected in EGFR-TKI-naive tumor samples, yet findings concerning the clinical impact of the minor T790M mutation vary among previous studies. In the present study, we assessed the clinical impact of the minor T790M mutation using a novel, highly sensiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 37 publications
1
19
0
Order By: Relevance
“…However, several studies have recently indicated that primary T790M mutation was present in a minor subgroup of patients prior to the TKIs treatment . The prevalence of primary T790M mutation varied by different detection methods, ranging from 0.5%–79% . However, this variation might be due to the false‐positive rate caused by highly sensitive methods used in clinical molecular testing .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…However, several studies have recently indicated that primary T790M mutation was present in a minor subgroup of patients prior to the TKIs treatment . The prevalence of primary T790M mutation varied by different detection methods, ranging from 0.5%–79% . However, this variation might be due to the false‐positive rate caused by highly sensitive methods used in clinical molecular testing .…”
Section: Discussionmentioning
confidence: 99%
“…With the emergence of osimertinib and high sensitivity detection method, primary T790M mutation attracted more attention . In the past, several specialists regarded primary T790M mutant as a poor prognostic factor due to its extremely poor response to first TKIs . Although primary T790M mutant patients showed better response to osimertinib, the median OS for primary T790M mutation patients was worse compared to that of acquired T790M mutation patients (29.9 months vs .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations